The Effect of Work Ethics and Work Discipline on Employee Performance at PT. PLN (Persero) Implementing Tello Power Control Unit, Makassar City - Patta Rapanna; Andi Sulfati; Mursidah Mursidah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine whether work ethics and work discipline have an effect on employee performance at PT.PLN (Persero) Tello Makassa Cityr's Generation Control Unit. Collecting data using primary data obtained from questionnaires using a saturated sample technique. The population is all employees in PT. PLN (Persero) Tello Makassar City Generating Control Unit as many as 67 people. The results of the research variable data have been tested by instruments in the form of validity and reliability tests, on the classical assumptions in the form of normality assumptions, multicollinearity tests and heterooxidity tests. Methods of data analysis using multiple linear regression analysis tests. As well as hypothesis testing using partial test, simultaneous test and coefficient of determination. The results of this study indicate that between the two independent variables, work ethics and work discipline variables have an influence on employee performance. This is evidenced by testing on the simultaneous test which has positive and significant results, meaning that both variables are able to improve employee performance.